Ecological ambivalence, complexity, and change perspectives from the Environmental Humanities - Müller, Simone M. 1982-; Schmidt, Matthias; Twelbeck, Kirsten (Routledge, 2025)
This book provides a systematic, interdisciplinary analysis of the conflicts, issues and tensions associated with today's ecological transformation processes from an environmental humanities perspective. Of interest to researchers, academics and students studying environmental humanities, the social sciences and environment sciences.
Keywords: Ökologie; Klimaänderung; Geisteswissenschaften; Gesellschaft; Environmental sciences-Philosophy; Science and the humanities; Aufsatzsammlung